2011
DOI: 10.1111/j.1440-1843.2011.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Sputum zinc concentration and clinical outcome in older asthmatics

Abstract: These findings suggest that sputum [Zn] reflect clinical outcomes and underlying AI, suggesting a potential role for zinc as a biomarker in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
2
18
0
2
Order By: Relevance
“…Plasma Zn constitutes less than 1% of total body Zn [42] and estimations based on blood may therefore not be representative for the level of free or loosely bound levels of Zn in airway tissue. We have recently shown that the levels of Zn ions in induced sputum are decreased in older patients with asthma [43]. Measuring Zn levels in bronchial brushings presents a technical problem in that these brushings are not routinely performed in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma Zn constitutes less than 1% of total body Zn [42] and estimations based on blood may therefore not be representative for the level of free or loosely bound levels of Zn in airway tissue. We have recently shown that the levels of Zn ions in induced sputum are decreased in older patients with asthma [43]. Measuring Zn levels in bronchial brushings presents a technical problem in that these brushings are not routinely performed in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Several studies observed the association between low zinc statuses either in serum, hair or sputum and asthma prevalence. 12-17 A small number of studies have been conducted to evaluate the efficacy of zinc supplementation for improvement lung functions or clinical symptoms of asthma during non-exacerbation; however, the results were not consistent. 18-20 Up to present, there is no report of zinc supplementation improving the clinical severity during asthmatic exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…17 Başka bir çalışmada ise 114 yaşlı astımlıda astım şiddeti ve FEV1 değeri labil balgam çinko düzeyi ile korele bulunmuştur. 42 El Khoyl ve ark. tarafından yapılan 22 astımlı hasta ve 20 kontrol grubunun karşılaştırıldığı bir çalışmada saç ve serum çinko düzeyleri düşük bulunmuştur.…”
unclassified